2016
DOI: 10.2174/1874350101609010111
|View full text |Cite
|
Sign up to set email alerts
|

The Romantic Jealousy as Multidimensional Construct: A Study on the Italian Short Form of the Multidimensional Jealousy Scale

Abstract: Abstract:Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…El instrumento fue desarrollado para evaluar los aspectos cognitivos, emocionales y conductuales de los celos en relaciones románticas. Diversos estudios informan buenos índices de consistencia interna superiores a .80 (Elphinston, Feeney, & Noller, 2011;Haas Bueno & Carvalho, 2005;Lucas, Pereira, & Esgalhado, 2012;Pfeiffer & Wong, 1989;Tani & Ponti, 2016); en Argentina se obtuvieron valores de coeficiente Alfa de .90, .86, .88 y .88 para las subescalas Cognitiva; Emocional; Comportamental y para el total, respectivamente (Delucchi et al, 2020). Para la muestra del presente estudio, los valores fueron .92, .87, .93 y .87, respectivamente.…”
Section: Instrumentosunclassified
“…El instrumento fue desarrollado para evaluar los aspectos cognitivos, emocionales y conductuales de los celos en relaciones románticas. Diversos estudios informan buenos índices de consistencia interna superiores a .80 (Elphinston, Feeney, & Noller, 2011;Haas Bueno & Carvalho, 2005;Lucas, Pereira, & Esgalhado, 2012;Pfeiffer & Wong, 1989;Tani & Ponti, 2016); en Argentina se obtuvieron valores de coeficiente Alfa de .90, .86, .88 y .88 para las subescalas Cognitiva; Emocional; Comportamental y para el total, respectivamente (Delucchi et al, 2020). Para la muestra del presente estudio, los valores fueron .92, .87, .93 y .87, respectivamente.…”
Section: Instrumentosunclassified
“…Research on adult attachment has shown that those high in attachment anxiety are more likely to monitor partner behavior as they seek assurance of continued interest, and are more likely to perceive emotional and sexual threats to their relationships (White and Mullen, 1989). They experience jealousy more frequently and intensively than avoidant and securely attached individuals, and respond to jealousy-provoking situations with more fear, anger, and sadness (Sharpsteen and Kirkpatrick, 1997;Guerrero, 1998;Rodriguez et al, 2015;Tani and Ponti, 2016).…”
Section: Attachment Anxiety and Jealousymentioning
confidence: 99%
“…The Multi-Dimensional Jealousy Scale (MJS) is translated into different languages, such as Italian. Tani and Ponti (2016) estimated the MJS factor structure using a sample of 361 people with a mean age of 26.50. The original scale factor structure has a satisfactory internal consistency of .80 to.85.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%